Notes on Early Land Plants Today. 8. New combinations and some lectotypifications in Mesoptychia - Váňa, Jiří; Söderström, Lars; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2012)
Mesoptychia sahlbergii (Lindberg & Arnell 1889) Evans (1903), was shown by de Roo et al. (2007), Vilnet et al. (2011) and Masuzaki et al. (2010) to belong to Jungermanniaceae and to be a sister of or nested within Leiocolea (Müller 1913) Buch (1933). The type of the genus Hattoriella (Inoue 1957) Inoue (1961a) [Hattoriella diversiloba (= H. morrisoncola)] is also nested within Leiocolea (Yatsentyuk et al. 2004). The three genera Mesoptychia, Leiocolea and Hattoriella should thus be regarded as one. Since the oldest genus is Mesoptychia, the necessary new combinations are made here.